The need to provide ad hoc precautionary measures for cases of disability: a critical analysis of the Preliminary Draft of LECrim 2020 - Pilar Martín-Ríos (Revista Brasileira de Direito Processual Penal, 2021)
In this paper we address a question of undoubted topicality and relevance: the application of criminal precautionary measures to subjects in whom a situation of disability exists. The analysis of this issue is framed in a legislative context that is particularly conducive to this, since the recent Draft of LECrim could led to a substantial change in this matter. Despite the general favorable assessment that this reform could deserve, this study highlights various aspects in need of review and different problems that the proposed regulation may lead to. In sum, can it be concluded that the projected norm sufficiently fulfills the expectations placed in this regard?